Pengaruh Isian Jenis Bola Kaca terhadap Dinamika Tetes dan Koefisien Pindah Massa Ekstraksi Cair-Cair dalam Kolom Isian - Agus Mirwan; Doni Rahmat Wicakso (INFO-TEKNIK, 2008)
Solvent extraction or Liquid-liquid extraction in packed column is a process of liquid phase separation in which a liquid solution (the feed) is contacted with an immiscible or nearly immiscible liquid (solvent). Mass transfer process occurs as effect of contact between continuous phase from above and dispersed phase from underside column. With existence of packing in column, that caused interfacial area to become bigger and residence time more and older so that improvement of mass transfer process. The aim of this research is to study drop dynamics or movement behavior of drop and mass transfer liquid-liquid extraction in packed column deputizing with overall mass transfer coefficient based on packing type of sphere. Drop shows different behavior at different packing type and height in column. The behavior will be caused changing in number of drop and drop size distribution along size column. Observation of drop behavior is done by using length square column transparent so that visually drop dynamics can be observed and recorded at every segment of column height using digital camera. This research will be done by packing type of sphere and varying flow rate of the dispersed phase to know behavior of drop. Besides this research will also be done observation of mass transfer rate from continuous phase to dispersed phase poured in the form of overall mass transfer coefficient. The research will be done by using water – MEK (methyl ethyl ketone) – n-hexane system. The result of this research for packing type of sphere shows that more and more big dispersed phase flow rate and height from under side column (distributor), hence drop is more and more small with number of which more and more many. This caused significant increase on overall mass transfer coefficient.